THE INFLUENCE OF MICRO, SMALL AND MEDIUM ENTERPRISE ACTORS’ KNOWLEDGE ABOUT SHARIA’ BANKING TOWARDS THEIR INTEREST TO USE MUSYARAKAH FINANCING PRODUCT - Anissa Arum Lestari; Siti Nur Azizah (Journal of Islamic Economy and Business (JIsEB), 2020)
Purpose: This research is conducted to observe the effect of Micro, Small and Medium Enterprises (MSME) agents’ sharia Banking Knowledge toward their interest of choosing musyarakah as financing product. Background Problems: MSME is a great potential market for financial service industry to distribute financing. Sharia banking has product in the form of profit sharing called musyarakah. Novelty: This study not only focuses on the knowledge of the public in general as customers of ordinary Islamic banks. Furthermore, research that uses knowledge factors such as Islamic work ethics, operational principles of Islamic banking, Islamic banking products, profit sharing, and financing risk is still relatively small Research Methods: The independent variable is knowledge that consists of Islamic work ethic in sharia banking knowledge, operational principle in sharia banking knowledge, knowledge of products in sharia banking, knowledge of profit sharing in sharia banking, risk of funding in sharia banking knowledge while the dependent variable is the interest to use musyarakah as financing product. The data analysis applies descriptive and multiple linear regression analysis. Results: Knowledge of products in sharia banking significantly affects the interest to use musyarakah as financing product, knowledge of Islamic work ethic in sharia banking, knowledge of profit sharing in sharia banking , knowledge of financing risk in sharia banking affect insignificantly toward the interest to choose musyarakah as financing product. Conclusion: The MSME actors have knowledge of Islamic banking that is not yet strong, because four of the five variables of knowledge about Islamic banking used in this study have no significant influence.Islamic work ethic, operational principle of sharia banking, sharia banking products, profit sharing of sharia banking, financing risk of sharia banking, musyarakah financing.